Bifunctional iron molybdate as highly effective heterogeneous electro-Fenton catalyst and Li-ion battery anode. (January 2022) - Santhoshkumar, P.; Hussain, Sajjad; Vikraman, Dhanasekaran; Karuppasamy, K.; Hussain, Tassawar; Ramesh, Sivalingam; Kim, Heung Soo; Kim, Hyun-Seok
Abstract: Three-dimensional materials have attracted considerable interest in energy and environmental remediation fields. Iron molybdate (FMO) materials have prepared via a facile hydrothermal technique with glycerol assistance, and their structural and chemical composition confirmed using various physico-chemical techniques. The prepared bi-functional material is a strong candidate for energy storage and electrocatalytic degradation of Methylene blue and Congo red. Experimental results confirmed the synthesized FMO-10 catalyst was extremely efficient for methylene blue and Congo red breakdown, achieving 91 % and 96 % degradation in 36 h, respectively. This high catalytic activity was attributed to FMO significant visible light absorption, and reactive OH formation from H2 O2 synergistically triggered by both Fe 3+ and MoO4 2− . Prepared FMO samples demonstrated excellent potential as negative electrode material for lithium ion batteries. Electrode specific capacity initially dropped then rebounded to 1265 mAh g −1 after 100 cycles at 100 mA g −1 change rate between 0.01 and 3.0 V. Graphical abstract: Image 1 Highlights: Template free hydrothermal technique was used for heterogeneous iron molybdate. Different amount of glycerol was used to synthesize iron molybdate. The prepared FMO-10 exhibits the highest surface area of 64 m 2 g −1 among the prepared samples. The prepared FMO-10 offered CR and MB degradation of 91 % and 96 %.